Mist1+ gastric isthmus stem cells are regulated by Wnt5a and expand in response to injury and inflammation in mice. Issue 4 (24th July 2020) - Nienhüser, Henrik; Kim, Woosook; Malagola, Ermanno; Ruan, Tuo; Valenti, Giovanni; Middelhoff, Moritz; Bass, Adam; Der, Channing J; Hayakawa, Yoku; Wang, Timothy C
Abstract : Background and aims: The gastric epithelium undergoes continuous turnover. Corpus epithelial stem cells located in the gastric isthmus serve as a source of tissue self-renewal. We recently identified the transcription factor Mist1 as a marker for this corpus stem cell population that can give rise to cancer. The aim here was to investigate the regulation of the Mist1+ stem cells in the response to gastric injury and inflammation. Methods: We used Mist1CreERT;R26-Tdtomato mice in two models of injury and inflammation: the acetic acid-induced ulcer and infection with Helicobacter felis . We analysed lineage tracing at both early (7 to 30 days) and late (30 to 90 days) time points. Mist1CreERT;R26-Tdtomato;Lgr5DTR-eGFP mice were used to ablate the corpus basal Lgr5+ cell population. Constitutional and conditional Wnt5a knockout mice were used to investigate the role of Wnt5a in wound repair and lineage tracing from the Mist1+ stem cells. Results: In both models of gastric injury, Mist1+ isthmus stem cells more rapidly proliferate and trace entire gastric glands compared with the normal state. In regenerating tissue, the number of traced gastric chief cells was significantly reduced, and ablation of Lgr5+ chief cells did not affect Mist1-derived lineage tracing and tissue regeneration. Genetic deletion of Wnt5a impaired proliferation in the gastric isthmus and lineage tracing from Mist1+ stem cells. Similarly, depletion of innate lymphoid cells, the main source of Wnt5a, also resulted in reduced proliferation and Mist1+ isthmus cell tracing. Conclusion: Gastric Mist1+ isthmus cells are the main supplier of regenerated glands and are activated in part through Wnt5a pathway.